Reconstructing the Business Model Canvas to Promote Sustainability in Community-Based Businesses - Akbar, Bintang Mukhammad Burhanudin Akbar; Soegesty, Nugraha Bagoes Soegesty (ICON Publisher, 2025)
The transformation of the national and regional economic structure has positioned micro, small, and medium enterprises (MSMEs) as key drivers of local economic growth; however, many still rely on conventional business models that neglect sustainability aspects. This study aims to reconstruct the Business Model Canvas (BMC) for tofu-based community industries in Depok and Bogor to integrate social and environmental dimensions within business practices. Using a descriptive qualitative approach and a case study design, data were collected through in-depth interviews, participatory observations, and focus group discussions with tofu producers, community leaders, and relevant stakeholders, complemented by secondary data from official reports and literature. The analysis employed thematic interpretation supported by the Triple Bottom Line framework to identify potential restructuring of BMC components. The findings reveal that existing tofu businesses focus mainly on production and direct sales with limited innovation, weak waste management, and dependence on imported soybeans. The reconstructed BMC emphasizes green partnerships, waste-to-product innovation, eco-branding, and digital marketing strategies that enhance economic resilience and social inclusion. The integration of environmental costs and benefits within the cost and revenue structure demonstrates that sustainability can generate new economic value rather than financial burdens. In conclusion, this study provides a strategic framework for sustainable community-based businesses, contributing to the development of inclusive and environmentally responsible local economies.